Differences across place and time in household expenditure patterns: Implications for the estimation of equivalence scales - Angela Daley; Thesia Isedora Garner; Shelley A. Phipps; Eva Sierminska (Luxembourg Income Study (LIS), 2020)
Equivalence scales are often used to adjust household income for differences in characteristics that affect needs. For example, a family of two is assumed to need more income than a single person, but not double due to economies of scale in consumption. However, in comparing economic well-being across countries and/or time, we ask whether it is appropriate to use the same equivalence scale if consumption expenditure patterns differ? We estimate equivalence scales for eight countries with data ranging from 1999 to 2012, using the same Engel approach in all cases. We find considerable variation in economies of scale across countries and some increases over time. Notably, we find that economies of scale are generally larger than those implied by the 'square root of household size' equivalence scale. Our results have important implications when deciding whether to use a common equivalence scale in comparisons of economic well-being across place and time.
Keywords: D12; I31; 330; economic well-being; Engel; necessities; equivalence scale; economies of scale; poverty